A RECONSTRUÇÃO HISTÓRICA DO COLÉGIO COLÔNIA HOLANDESA- ARAPOTI-PARANÁ (1960-2013) - Camargo, Carla Roseane de Sales (2016)
The objective of this research is to investigate the historical process of reconstitution of the College Dutch colony in Arapoti-PR, which covers the period since the arrival of these immigrants in arapoti in 1960 until 2013. We used the methodology of oral history (collection six oral testimony) combined with the analysis of documentary sources (the political-pedagogical project and the school regulations), as well as a literature review on school management. Thus, there was an analysis of the context of reconstruction of the College Cologne Dutch from the arrival of Dutch immigrants in Arapoti in the early 1960s, seeking to identify the factors contributing to output the same to their homeland and coming to the Brazil; identify the design of school education, and analyze the role of managers in the identity construction of the same. To achieve these objectives, the research was structured and organized with theoretical and methodological framework of Oral History Goldenberg (2002) and Alberti (2004), using as a theoretical Hall (2002) and Pollak (1992) and about the school management Libâneo (2004) and Paro (2000). Due to difficulties in finding documents, there was emphasis on testimonials because through the memory of the interviewees, we seek to reconstruct the history of education of these immigrants in Arapoti-PR. However, despite the efforts, we know that this story will always remain unfinished. Thus, the developed research sought to contribute to the expansion of knowledge in the field of History of Brazilian Education, through a local crop, the education of Dutch immigrants in Arapoti-PR.